The connection between climate change and malnutrition - Bliznashka, Lilia; Iruhiriye, Elyse (Welthungerhilfe, 2025)
The linkage is increasingly being acknowledged by policies and in climate protection measures. But concrete, well-financed and institutionally backed strategies are still lacking.